The Effect of Inquiry Based Learning With V-Diagram on Students Science Process Skills in Provision Solution Materials - Hutapea, Risme; Copriady, Jimmi; Rasmiwetti, Rasmiwetti (FKIP-Universitas Riau, 2020)
Process skills are very important to be trained for students in the learning process because process skills have a role to help students in developing their minds, provide opportunities to make discoveries, improve memory, and help students learn scientific concepts. The purpose of this research was to determine the effect of inquiry-based learning on students' science process skills in the buffer solution material. The research method used a quasy experiment with a research design Posttest Only Control Group Design, which consists of an experimental class and a control class. The results showed that inquiry-based learning with V-diagrams had a higher score of student science process skills than those using inquiry-based learning alone. Generally the inquiry-based learning with V-diagrams is more effective than inquiry-based learning for students' science process skills.